A Descriptive Analysis of Tuberculosis Deaths in Bandar Lampung City, Indonesia, 2017–2021 - Sitti Fadhilah Milu; Santri Fitran Umanahu; Rufianti; Syarifah Aisiyah Syaqila; Rusmin (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Tuberculosis (TB) remains a major global public health problem, including in Indonesia, and is explicitly targeted for control and elimination within the Sustainable Development Goals (SDGs). TB is caused by Mycobacterium tuberculosis, which primarily affects the lungs but may also involve other organs. Indonesia is among the countries with the highest TB burden worldwide. In Lampung Province, particularly in Bandar Lampung City, TB cases have shown an increasing trend over recent years. TB transmission and outcomes are strongly influenced by nutritional status, host immunity, patients’ knowledge and behavior, as well as persistent social stigma, which often leads to delayed diagnosis and poor treatment adherence. Therefore, evidence-based control efforts, including systematic surveillance and data-driven monitoring, are essential to better understand disease patterns and inform effective interventions. Objective: This study aimed to describe the distribution of tuberculosis-related deaths in Bandar Lampung City during the period 2017–2021 based on secondary data from the municipal health profile. Methods: A quantitative descriptive study design was employed using secondary data obtained from the Bandar Lampung City Health Profile. Data on annual TB-related deaths were analyzed descriptively by organizing them into tables and graphical presentations, followed by narrative interpretation to identify temporal patterns and trends. Results: The findings indicate fluctuations in the tuberculosis case notification rate (CNR), with the highest level observed in 2019 and a marked decline in 2020 during the COVID-19 pandemic. The proportion of TB cases among children was relatively low (35.1%), suggesting limitations in contact tracing and early case detection. Furthermore, the bacteriologically confirmed TB cure rate in 2021 was only 55.6%, reflecting challenges in treatment adherence and program effectiveness. TB-related mortality during treatment remained high, with 65 reported deaths, highlighting gaps in service quality and patient monitoring. Conclusion: TB control in Bandar Lampung City continues to face substantial challenges, including unstable case reporting, low detection among children, suboptimal cure rates, and high mortality during treatment. Strengthening surveillance systems, improving health worker capacity, and ensuring equitable quality of TB services across health facilities are critical to improving TB control outcomes.